Cytological and microbiological examination of bovine milk in Prototheca-infected dairy herd: Preliminary report - Turbók, Janka; Tornyos, Gábor; Kocsis, Róbert; Süle, Judit; Tóth, Tamás; Buzás, Henrietta; Szafner, Gábor; Ács, Virág; Zomborszky, Zoltán (Acta Agraria Kaposváriensis, 2022)
In healthy milk the somatic cell count (SCC) is less than 100.000 cells per mL, although in the presence of infectious agents, especially pathogenic bacteria, SCC can be extremely high. Cytological appearance of inflammation in mammary gland depends on the origin and the time-course of the inflammatory response. According to predominant cell type there can be suppurative, pyogranulomatous, granulomatous and lymphocytic inflammation. Prototheca spp. as facultative pathogen creates chronic inflammation in mammary gland with high SCC and reduced milk production. The aim of our study was to elaborate a practical and accurate laboratory procedure to enhance the precision of milk somatic cell differentiation, and to provide quick and easy-to-perform detection for the presence of infectious algae in mastitis cases. In 95 quarter samples SCC was determined by California Mastitis Test, cellular density estimation and somatic cell differentiation were carried out by microscopically evaluation, while presence of Prothoteca spp. was investigated with the help of specific culture medium (PIM agar). According to CMT results, SCC values showed 67.3% prevalence of mastitis, from which 6.3% was clinical and 93.7% subclinical. Comparing CMT results and estimated cellularity values indicated tight correlation. In CMT negative quarters 60% of somatic cells were neutrophil granulocytes, while in CMT positive but Prototheca spp. negative cases these cells were present in 74%. Interestingly in Prototheca spp. positive samples only 60.25% of cells were neutrophil granulocytes, while macrophages and lymphocytes were present in 17% and 18.3%, respectively. Moreover, remarkable cytological pattern was notified in some samples that were positive for Prototheca spp., and statistical analysis showed tight correlation between infectious algae and the ratio of macrophages (p=0.005). In conclusion laboratory techniques applied in our study seems to be helpful supplementary methods to reveal pathological background of mastitis as well as to monitor the progression of inflammatory reactions.Acknowledgment: This publication was supported by the EFOP-3.6.3-VEKOP-16-2017-00008 „Innovative scientific  workshops  in  the Hungarian  agricultural higher education”. The project was co-financed by the European Union and the European Social Fund.
Keywords: mastitis; somatic cell count; infectious algae; cytology; cattle